The Influence of Digital Marketing Strategy on Business Growth in the Digital Era (case study on the e-commerce industry) - Luwiha, Luwiha; Karsinah, Karsinah; Julianti, Mega; Prayoga, Andi (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2024)
The general aim of the research is to determine whether or not there is an influence of digital marketing strategies on business growth in the digital era. The hypothesis of this research is that there is an influence of digital marketing strategies on business growth in the digital era. The subjects of this research are consumers who use e-commerce. The subjects of this research consisted of men and women aged 18-23 years, totaling 70 people at the time of the trial and 70 people at the time the research data was collected. The data collected through the scale is then distributed to research subjects. The data was then analyzed statistically using multiple regression analysis with SPSS version 16.0 for Windows. The results of the analysis obtained a value of R = 0.965 with p = 0.000 (p<0.01). The coefficient of determination (R-Square) of digital marketing strategies on business growth in the digital era is 60.3% (0.603). The general conclusion from this research is that there is a very significant positive influence of digital marketing strategies on business growth in the digital era. The higher the digital marketing strategy provided by employees, the higher the business growth in the digital era. Thus, this research concludes that digital marketing strategies have a significant influence on business growth in the digital era. Businesses that are able to combine digital marketing techniques with a strong understanding of markets and technology will have a better chance of achieving sustainable growth and long-term success.